Lookup Tables Versus Stacked Rasch Analysis in Comparing Pre- and Postintervention Adult Strabismus-20 Data - Leske, David A. (Transl Vis Sci Technol, 2016)
PURPOSE: We compare two methods of analysis for Rasch scoring pre- to postintervention data: Rasch lookup table versus de novo stacked Rasch analysis using the Adult Strabismus-20 (AS-20). METHODS: One hundred forty-seven subjects completed the AS-20 questionnaire prior to surgery and 6 weeks postoperatively. Subjects were classified 6 weeks postoperatively as “success,” “partial success,” or “failure” based on angle and diplopia status. Postoperative change in AS-20 scores was compared for all four AS-20 domains (self-perception, interactions, reading function, and general function) overall and by success status using two methods: (1) applying historical Rasch threshold measures from lookup tables and (2) performing a stacked de novo Rasch analysis. Change was assessed by analyzing effect size, improvement exceeding 95% limits of agreement (LOA), and score distributions. RESULTS: Effect sizes were similar for all AS-20 domains whether obtained from lookup tables or stacked analysis. Similar proportions exceeded 95% LOAs using lookup tables versus stacked analysis. Improvement in median score was observed for all AS-20 domains using lookup tables and stacked analysis (P < 0.0001 for all comparisons). CONCLUSIONS: The Rasch-scored AS-20 is a responsive and valid instrument designed to measure strabismus-specific health-related quality of life. When analyzing pre- to postoperative change in AS-20 scores, Rasch lookup tables and de novo stacked Rasch analysis yield essentially the same results. TRANSLATIONAL RELEVANCE: We describe a practical application of lookup tables, allowing the clinician or researcher to score the Rasch-calibrated AS-20 questionnaire without specialized software.